Educational Interventions in Adults with Type 2 Diabetes Mellitus in Primary Health Care Settings. A Scoping Review - Castillo-Merino, Yasmin Alejandra; Ospina-Ayala, Camila; Esquivel Garzón, Natalia; Rodríguez-Acelas, Alba Luz; Cañon-Montañez, Wilson (Investigación y Educación en Enfermería, 2023)
Objective. To synthesize the evidence of studies with educational interventions for adults with type-2 diabetes mellitus (DM2) in primary health care settings. Methods. A scoping review was conducted following the recommendations by the Joanna Briggs Institute and by the PRISMA declaration. The protocol was registered in INPLASY20215009. The search was carried out in: MEDLINE (via PubMed), EMBASE, Web of Science, LILACS, and grey literature. Results. Seventeen studies were included; most were randomized clinical trials of which 65% were conducted in high-income countries, and all the studies represented 5 656 participants. The results showed four big categories derived from educational interventions: therapeutic adherence (significant results on the satisfaction with the treatment); self-care and self-management in diabetes (improvement in self-efficacy, empowerment, and disease awareness); glycemic control in diabetes (significant results in reducing glycosylated hemoglobin); nursing and its role in the educational interventions on patients with DM2 (guidance in restructuring behaviors). Conclusion. The findings of this review suggest that educational interventions on patients with DM2 within the setting of primary health care can impact positively on therapeutic adherence, self-control, and knowledge of the disease. Moreover, it was possible to identify the influence of multidisciplinary health teams, where the relevance of nursing professionals in the construction and implementation of educational interventions is evidenced in obtaining better health results.